Multidimensional Impacts on Bryophyllum Pinnatum for the Potential of Obesity: A Review - Varun Mishra; Sarbjot Singh; Rajneesh Kaur; Brij Bhushan; Shruti Jaswal; Anita Devi; Anuneet Kaur (International Journal of Biochemistry and Biomolecule Research, 2024)
Global public health concerns related to obesity are growing. Several comorbid illnesses, including cardiovascular disease (CVC), gastrointestinal disorders, type 2 diabetes (T2d), joint and muscle disorders, respiratory difficulties, and psychological disorders, are significantly more common in obese patients. The widespread misconception that obesity stems solely from a lack of self-control is gradually losing its stigma as awareness about fat-related issues grows. Instead of synthetic drugs herbal or medicinal plants are much beneficial in the treatment of obesity. Bryophyllum pinnatum leaves have been employed as an antibiotic in traditional medicine. So, in this paper we reviewed that plant have various pharmacological effects on the body with very less side effects and their active phytoconstituents have an soothing effect to get rid of obesity.
Keywords: Bryophyllum Pinnatum; Medicinal Plants; obesity; phytoconstituents; synthetic drugs